Evaluation of the association of mucosa-associated invariant t (mait) cells with childhood asthma - Ekşi, Meral; Bulut, Huri; Akalın, Erdem; Ustabaş Kahraman, Feyza; Yazan, Hakan; Yazıcı, Mebrure; Çakır, Erkan (My University, 2024)
Background/aim: Innate-like T lymphocytes are a recently defined group of T cells comprising mainly mucosa-associated invariant T (MAIT) cells. The relationship between MAIT cells and childhood asthma is controversial. In this study, we aimed to determine the role of MAIT cells in patients with allergic asthma (AA) and nonallergic asthma (NAA). This is the first study to compare the ratios of these cells in patients with AA and NAA. Materials and methods: The study included children aged 6–18 years with AA (n = 41) or NAA (n = 30) and healthy control subjects (n = 36). The control group consisted of children who presented to the outpatient clinic without chronic disease, malnutrition, or acute or chronic infection. The proportions of MAIT, TH17, MAIT-17, and Th17-17 cells were investigated by flow cytometry and compared among the AA, NAA, and control groups. Results: When the AA and NAA patient groups were compared, the mean MAIT cell ratio was significantly lower in NAA patients (median: 0.45, p < 0.05). MAIT cell ratios were also substantially lower in NAA patients compared to the control group (mean: 0.504, p < 0.05). TH17, MAIT-17, and TH17-17 cell values were not statistically significant among the groups. Conclusion: Our study found that MAIT cell ratios were lower in the NAA patient group compared to the control group and AA patients. It has been predicted that MAIT cell depletion may have a role in the development of NAA. Our study is the first on this subject in the literature and further studies are needed.
Keywords: Allergy; Childhood Asthma; Innate Cells; Interleukin 17; Mucosa-Associated Invariant T Cells; T Helper 17 Cell